Different heart failure phenotypes of valvular heart disease: the role of mitochondrial dysfunction - Zhang, Shenghui; Liu, Cheng; Zhang, Yingyuan; Wu, Zongjian; Feng, Kaiwei; Lai, Yanxian; Pei, Jingxian; Guan, Tianwang (Frontiers in Cardiovascular Medicine, 2023)
Valvular heart disease (VHD) originated heart failure (HF) is a special subtype of HF with an increasingly concerned heterogeneity in pathophysiology, clinical phenotypes and outcomes.The mechanism of VHD related HF involves not only mechanical damage to the valve itself but also valve lesions induced myocardial ischemia, and the interactions between them will lead to the occurrence and development of VHD related HF subtypes. Due to the spatial (combination of different valvular lesions) and temporal effects (sequence of valvular lesions) of valvular damages, it can make the patient's condition more complicated, and also make physicians in a dilemma when determining the treatment plan. This indicates that there is still lack of fully understanding on the pathogenetic mechanism of VHD related HF subtypes. On the other hand, Mitochondrial dysfunction (MitD) is not only associated with the development of numerous cardiac diseases such as atherosclerosis, hypertension, diabetes, and HF, but also occur in VHD. However, the role of MitD in VHD related HF is still not fully appreciated. In this comprehensive review, we aimed to discuss the current findings and challenges of different valvular demages originated HF subtypes as well as the role of MitD in VHD related HF subtypes.